Influence of patient and tumor characteristics on therapy persistence with letrozole in postmenopausal women with advanced breast cancer: results of the prospective observational EvAluate-TM study - Wallwiener, Markus; Nabieva, Naiba; Feißt, Manuel; Fehm, Tanja (BMC cancer, 2019)
Background - Treatment of postmenopausal, hormone receptor-positive metastatic breast cancer (MBC) patients varies despite clear therapy guidelines, favoring endocrine treatment (ET). Aim of this study was to analyze persistence of palliative aromatase inhibitor (AI) monotherapy in MBC patients. - - Methods - EvAluate-TM is a prospective, multicenter, noninterventional study to evaluate treatment with letrozole in postmenopausal women with hormone receptor-positive breast cancer. To assess therapy persistence, defined as the time from therapy start to the end of the therapy (TTEOT), two pre-specified study visits took place after 6 and 12 months. Competing risk survival analyses were performed to identify patient and tumor characteristics that predict TTEOT. - - Results - Out of 200 patients, 66 patients terminated treatment prematurely, 26 (13%) of them due to causes other than disease progression. Persistence rate for reasons other than progression at 12 months was 77.7%. Persistence was lower in patients who reported any adverse event (AE) in the first 30 days of ET (89.5% with no AE and 56% with AE). Furthermore, patients had a lower persistence if they reported compliance problems in the past before letrozole treatment. - - Conclusions - Despite suffering from a life-threatening disease, AEs of an AI will result in a relevant number of treatment terminations that are not related to progression. Some subgroups of patients have very low persistence rates. Especially with regard to novel endocrine combination therapies, these data imply that some groups of patients will need special attention to guide them through the therapy process. - - Trial registration - Clinical Trials Number: CFEM345DDE19 - - Electronic supplementary material - The online version of this article (10.1186/s12885-019-5806-y) contains supplementary material, which is available to authorized users.